Ethnoscience Phenomenon: The Chemical Element Glucose as a Symbol of Human Enjoyment of Life in The Nyadran Celebration in Magelang - Wijaya, Raden Ary Bhagawan; Purwasita, Andrik; Rahmanto, Andre Novi (Postgraduate, University of Mataram, 2023)
The purpose of this study is to determine the symbolic meaning represented by the food that must be present in every nyadran performance in Magelang City. This study is a case study with ethnographic approach. With the guidance of symbolic interactionism theory, the meaning of the taste of the chemical elements of the food will be analyzed so that there is a scientific explanation present. The informants in this study are artists, art observers and nutritionists. The results of the study, ethnoscience representations appear when the previous artists even though they cannot parse the chemical elements of coffee that create bitterness. Likewise, in the chemical elements of bananas that cause sweetness. Bitter is a flavor that in chemistry is caused by the compound trigonelline (niacin), which is found in coffee. Sweetness is a flavor that, according to chemistry, is caused by glucose in bananas. According to the informants, the sweet and bitter flavors in the food that must be present at the event represent how human life is always filled with two dominant feelings, namely bitter which is a representative of sadness, difficulty, suffering and sweetness which represents pleasure, happiness.